Factors Influencing NGO Activities: Lithuanian Case Study - Stasiukynas, Andrius; Šukvietienė, Aušra; Sudnickas, Tadas (International Journal of Criminology and Sociology, 2022)
The article aims to explore the external and internal factors influencing the activities of NGOs, in Lithuania. A qualitative empirical study was conducted (10 expert surveys) on this issue, what are the factors that help and hinder the activities of NGOs in Lithuania. The study allowed us to identify groups of factors positively influencing the activities of NGOs: human skills; infrastructure, as well as the organisation’s relationship with public authorities, the hindering factors were also identified: the application of contracting authority status to NGOs; "activities in the public interest" interpretation; peculiarities of taxation of non-profit organizations; etc. The most relevant groups of NGO activity problems and related legal acts were distinguished: application of the contracting authority status to NGOs (Law on Public Procurement of the Republic of Lithuania); Interpretation of “activities in the public interest” (STI material. Peculiarities of taxation of non-profit organizations; etc. legislation); application of corporate income tax to non-profit organizations (Law on Corporate Income Tax of the Republic of Lithuania).